The coronary CT angiography vision protocol: a prospective observational imaging cohort study in patients undergoing non-cardiac surgery. Issue 4 (31st July 2012) - Sheth, Tej; Butler, Craig; Chow, Benjamin; Chan, M T V; Mitha, Ayesha; Nagele, Peter; Tandon, Vikas; Stewart, Lori; Graham, Michelle; Choi, G Y S; Kisten, T; Woodard, P K; et al.
Abstract : Introduction: At present, physicians have a limited ability to predict major cardiovascular complications after non-cardiac surgery and little is known about the anatomy of coronary arteries associated with perioperative myocardial infarction. We have initiated the Coronary CT Angiography (CTA) VISION Study to (1) establish the predictive value of coronary CTA for perioperative myocardial infarction and death and (2) describe the coronary anatomy of patients that have a perioperative myocardial infarction. Methods and analysis: The Coronary CTA VISION Study is prospective observational study. Preoperative coronary CTA will be performed in 1000–1500 patients with a history of vascular disease or at least three cardiovascular risk factors who are undergoing major elective non-cardiac surgery. Serial troponin will be measured 6–12 h after surgery and daily for the first 3 days after surgery. Major vascular outcomes at 30 days and 1 year after surgery will be independently adjudicated. Ethics and dissemination: Coronary CTA results in a measurable radiation exposure that is similar to a nuclear perfusion scan (10–12 mSV). Treating physicians will be blinded to the CTA results until 30 days after surgery in order to provide the most unbiased assessment of its prognostic capabilities. The only exception will be the presence of a left main stenosis >50%. This approach is supported by best available current evidence that, excluding left main disease, prophylatic revascularisation prior to non-cardiac surgery does not improve outcomes. An external safety and monitoring committee is overseeing the study and will review outcome data at regular intervals. Publications describing the results of the study will be submitted to major peer-reviewed journals and presented at international medical conferences.